The usage, self-presentation via Facebook, and its psychological and sociological consequences towards Saudi Arabia university students / Abdullah Ali Alassiri - Alassiri, Abdullah Ali (2015)
Prompted by the widespread saturation of Facebook usage in Saudi Arabia, among university students to socialize with online members, this study investigated the usage, self-presentation, psychological and sociological consequences of the Facebook social networking site among undergraduate students in Saudi Arabia. The problem statements of this study were addressed by answering the seven research questions: 1) What motivation does undergraduate students have for joining Facebook? 2) How undergraduate students do consume Facebook? 3) In what condition does undergraduate students need Facebook? 4) How do undergraduate students manage their self-presentation via Facebook? 5) What are the experiences obtained by the undergraduate students from Facebook psychologically? 6) What are the experiences obtained by the undergraduate students from Facebook sociologically? 7) How have Facebook activities affected the lifestyle of the undergraduate students? The research questions were answered by analysing in-depth interview data collected from twenty male undergraduate students between the ages of 18 and 24 years selected from King Saud University (KSU) and King Khalid University (KKU) Saudi Arabia. Using thematicanalysis, informants data were coded 'Rl to R20\ validated and was transcribed to minimize error from translating into the research items from Arabic back to English Language. Using purposive sampling method informant perspective within the research context were explored. Data collection confined to motivations students have for engaging in online activities, self-presentation, psychological and sociological consequences to their everyday life was investigated based on the theoretical and philosophical perspective underpinnings media and gratification paradigm and social influence theory. The research findings contributed to the development of important research themes that supported the development of a new research framework. Based on the analysis, all the research questions were answered. The findings foe this study showed that the students use Facebook for the prupose of interacting with others, getting information and as knowledge sources. In terms of self-presentation, this study revealed that the students portray theselves in real and not fake image while socializing with others.psychological and sociological consequences from the usage of Facebook are recorded ranging from cheerful to stress and from lonliness to having many friends. As a conclusion, this study conclusively drawn that Facebook is a very persuasive medium of communication among the University students in Saudi Arabia that bridges across socio-cultural boundaries and unites students to interact as a community.